Sorting in iterated incumbency contests - Samuel Häfner; Georg Nöldeke (University of Basel, Center of Business and Economics (WWZ), 2016)
This paper analyzes iterated incumbency contests with heterogeneous valuations in a large population setting. Incumbents repeatedly face different challengers, holding on to their positions until defeated in a contest. Defeated incumbents turn into challengers until they win a contest against an incumbent, thereby regaining an incumbency position. We consider steady-state equilibria of this process and study how and to which extend individuals sort into the incumbency positions depending on their valuations. In particular, we identify suffcient conditions for positive sorting, meaning that the share of individuals with a given valuation holding an incumbency position is increasing in the valuation, and provide an example to show that negative rather than positive sorting may arise in equilibrium. Further results show how incumbency rents and sorting are affected by the frequency at which incumbency is contested and the scarcity of the incumbency positions.
Keywords: C72; D72; D74; 330; Contests; Sorting; Incumbency Rents; Steady-State Equilibrium